Achieving sustainability in roller compacted concrete pavement mixes using reclaimed asphalt pavement aggregates – state of the art review. (10th March 2021) - Debbarma, Solomon; Ransinchung R.N., G.D.
Abstract: This paper presents a state-of-the-art review of the utilization of reclaimed asphalt pavement (RAP) aggregates in roller compacted concrete pavement (RCCP) mixes. Owing to the cost-effectiveness and fast-to-construct feature of RCCP, the utilization of RAP in this paving technology seems to be the next best option. In this paper, several issues and factors affecting the fresh and hardened properties of RCCP mixes due to the incorporation of RAP is discussed. Based on this review, it was observed that the type and age of RAP, the concentration of asphalt and agglomerated particles, gradation of RAP, compaction types and efforts, and the RAP replacement levels can significantly affect the strength and durability of RCCP mixes. From a sustainable point of view, most researchers recommended that up to 50% of RAP could be used to partially substitute natural aggregates in RCCP mixes. In a nutshell, the utilization of RAP in RCCP mixes would not only provide economic benefits but would also serve environmental benefits like reduction in the RAP stockpiles and carbon footprints, respectively.